Current Review on the Exploring Potential of TiO₂ Catalysts for Efficient Microplastic Removal from Aqueous Solutions - Mohammad Luqman Ismail; Norzahir Sapawe; Muhammad Farhan Hanafi; Hairul Amani Abdul Hamid; Siti Munirah Sidik (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This review explores the potential of titanium dioxide (TiO₂) catalyst for the removal of microplastics from aqueous solution, highlighting their photocatalytic properties, advantages, and challenges. TiO₂, as a widely studied and cost-effective photocatalyst, offers unique benefits for addressing the growing concern of microplastic pollution in water. The article examines various TiO₂-based materials, including pure TiO₂, doped TiO₂, and composite materials, and their effectiveness in degrading or removing microplastics through photocatalytic processes. Key factors such as light intensity, catalyst dosage, pH, and reaction time that influence the photocatalytic efficiency of TiO₂ catalyst are discussed. The review also explores the mechanisms of photocatalytic degradation, including the generation of reactive oxygen species (ROS) and the role of TiO₂ in breaking down microplastic polymers. Furthermore, challenges such as catalyst stability, reusability, and the need for optimization are addressed. The article concludes by proposing future research directions for enhancing the performance of TiO₂ catalyst and their potential application in large-scale water treatment for microplastic removal.